Simulation of mobile fading channel by using deterministic method - Wang, Xiao. (2008)
Due to the multipath propagation environment, the received signal suffers multipath fading. The amplitude and phase of received signal is subjected to abrupt changes. But in theory, these changes conform to certain principle. That is, the amplitude of received signal changes according to a specific probability distribution function, and so does phase. In frequency nonselective channel, we use a complex-valued stochastic process to represent the changes of amplitude and phase for received signal. The amplitude and phase of complex-valued stochastic process are also two stochastic processes, which are denoted as a(t) and 6(t). Thus, for received signal, the amplitude is product of transmitted signal's amplitude and a(t), and phase is the sum of the phase of transmitted signal and 6(t). So how to characterize the stochastic processes a(t) and 6(t) is important for us to study the frequency nonselective channel.